Hope or despair: a socio-legal study on the rights of undocumented children in Malaysia / Nuraini Roslan, Nur Azimah Che Ismail and Baizurah Mohd Nasir. - Roslan, Nuraini; Che Ismail, Nur Azimah; Mohd Nasir, Baizurah (2009)
This project paper is a social-legal review and study on the rights of undocumented children in Malaysia. undocumented children mean those who are without birth certificate or are unregistered with the National Registration Department of Malaysia. The focus is on the undocumented children of Malaysian parents which are deprived of their rights in their own country. This project paper shall cover the rights of children governed by the 1989 United Nations Convention on the Rights of the Child (CRC) and several other laws in Malaysia, such as the Child Act 2001. Besides that, the study will be on the relevancy of reservations in certain Articles by Malaysia in the CRC and also the reasons for children being undocumented and its consequences. The purpose of this paper is to review the laws that govern the rights of these undocumented children. If they are registered, then they are protected under the laws. Along the journey to complete this task, the researchers have discovered that there are quite a number of reasons for children being undocumented and numbers of very sad cases pertaining children being undocumented are phenomenal. The Government of Malaysia recognises that a child is the key to the country's survival, development and prosperity. Thus, it is hoped that the study will help Malaysians to gain awareness of the problems faced by children.